SANKSI PIDANA CAMBUK TERHADAP PELANGGARAN “QANUN” PADA BIDANG KHAMAR DI WILAYAH KOTA BANDA ACEH : Nelti Rianfika - admin, admin (Reformasi Hukum, 2017)
People who practice khamar or liquor is certainly very disturbing community. Especially if the khamar or liquor conducted in public. This is certainly very worrying, given that the child is the successor of the nation in the future. The method that used in this research is descriptive analystis. Implementation of criminal sanctions against perpetrators in the field of rooms will be accomplished perfectly if all parties are not together with courage as mandated by the Qur'an and Hadith is manifested in real action, it is not possible if submitted entirely to the Wilayatul Hisbah or the Police only. The implementation of the criminal sanction of the caning is effective enough to suppress the violation of qanun in the field of Islamic Shari'ah, as evidenced by the data showing the decrease of violation of qanun in Islamic Sharia in Banda Aceh City, but there are many more that must be addressed and perfected in the implementation of this Islamic Shariah either in the form of regulations or qanuns that have been established by the government of Nanggroe Aceh Darussalam Province, as well as in the implementation of the field, and the need for the addition of quality and quality of human resources in the city of Banda Aceh as implementing officers in the field. In implementing the Shari'ah of Islam in the Banda Aceh City Region the city government of Banda Aceh made various efforts in controlling the implementation of Islamic Shari'ah. In addition to mobilizing all elements of society to cooperate in the implementation of Islamic Shari'ah. Development of village structure proportionally, to maximize the community then in every village should need the addition of Islamic Shari'ah chapter led by the character who sourced from each village, for efficiency, then the addition of this Shari'ah Islam can be focused on villages with prominent sharia violations only.